On the Identity and Wood Structure of Connarus gibbusus Wall. - Pande, P. K.; Singh, Magan; Bisht, G. S. (Indian Forester, 2003)
The wood structure of Connarus gibbosus Wall. Is described in detail. It is a diffuse porous structure with moderately small to medium sized vessels, scanty vasicentric, aliform to confluent and marginal parenchyma, non.septate fibres 1-4 seriate heterogeneus rays, small scattered, vertical canals and small variable crystals in parenchyma, rays and fibres.